Diplopia and proptosis due to isolated lateral rectus plasmacytoma in a patient with multiple myeloma. Issue 7 (8th July 2019) - Saffra, Norman; Gorgani, Farzan; Panasci, David; Kirsch, David
Abstract : Orbital involvement of multiple myeloma (MM) is uncommon, with most of those reported cases occurring at the time of initial diagnosis of MM. We present a case of an extramedullary plasmacytoma involving only the right lateral rectus of a patient who had been in disease remission. The patient presented with new-onset diplopia and an abduction deficit of the right eye, with mild proptosis. In light of her past medical history of MM, an orbital MRI was obtained. The MRI demonstrated an isolated finding of eccentric enlargement of the right lateral rectus muscle limited to the muscle belly with sparing of the tendinous insertions, leading to diagnosis of plasmacytoma. Patching of the involved eye to alleviate the symptoms of diplopia was instituted. Chemotherapy was initiated, followed by orbital radiation and stem-cell transplantation for coexisting systemic disease. The orbital symptoms of proptosis and diplopia resolved within 1 month of treatment.